The Relationship Between Liver Enzymes and Insulin Resistance in Type 2 Diabetes Patients with Nonalcoholic Fatty Liver Disease - Sheng, Xia; Che, Hui; Ji, Qingming; Yang, Fan; Lv, Jie; Wang, Yueqiu; Xian, Huimin; Wang, Lihong (Hormone and Metabolic Research, 2018)
Non-alcoholic fatty liver disease (NAFLD) is prevalent worldwide, especially in patients with type 2 diabetes. Liver enzymes are the main warning signs of liver injury and insulin resistance (IR) is critical to NAFLD. This study was aimed to investigate the association between liver enzymes and insulin resistance in type 2 diabetes patients with NAFLD. Data from 212 diabetes patients with NAFLD were analyzed, including 118 males and 94 females who received care from 2014 to 2015. The patients were divided into three groups by severity (mild n=87, moderate n=89, severe n=36). All patients underwent standard clinical and laboratory examinations. Liver enzymes including alanine aminotransferase (ALT), aspartate aminotransferase (AST), and γ-glutamyl transferase (GGT) were measured, serum fasting glucose and serum fasting insulin were obtained. IR was assessed using the homeostasis model assessment insulin resistance index (HOMA-IR). Age, sex, and BMI did not significantly differ in patients (p>0.05). Compared with normal levels, elevated ALT and AST were associated with a higher HOMA-IR (p=0.0035, p=0.0096, respectively). HOMA-IR did not significantly differ (p>0.05) between patients with normal and elevated GGT. HOMA-IR increased as the levels of liver enzymes increased, and each enzyme showed a significant association with HOMA-IR (p=0.0166, p<0.0001, and p <0.0001). HOMA-IR differs between normal and elevated ALT and AST. Liver enzymes are associated with HOMA-IR in type 2 diabetes patients with NAFLD. These findings can help evaluate the degree of IR and hepatocellular steatosis in patients and prevent the progression of type 2 diabetes and NAFLD in clinical practice.
Keywords: non-alcoholic fatty liver disease (NAFLD); type 2 diabetes; insulin resistance (IR); alanine aminotransferase (ALT); aspartate aminotransferase (AST); γ-glutamyl transferase (GGT)